Selective permeabilisation of the blood-brain barrier at sites of metastasis. - Connell, JJ (2014)
Over one in five cancer patients will develop brain metastases and prognosis remains poor. Effective chemotherapeutics for primary systemic tumours have limited access to brain metastases owing to the blood-brain barrier (BBB). The aim of this study was to develop a strategy for specifically permeabilising the BBB at sites of cerebral metastases. Tumour necrosis factor was injected intravenously into mouse models of haematogenously induced brain metastasis. BBB permeability was assessed through histology and in vivo MRI and SPECT. Tumour burden and neuroinflammation were assessed after injection of TNF with Caelyx or a novel therapeutic. Mechanism of permeabilisation was investigated through histology and receptor-specific agonist antibodies. Administration of TNF dose-dependently permeabilised the BBB to exogenous tracers selectively at sites of brain metastasis, with peak effect after six hours. Metastasis-specific uptake of radiolabelled trastuzumab was also demonstrated following systemic cytokine administration. Administration of liposomal doxorubicin formulations in conjunction with TNF reduced tumour burden and mean metastasis size. Localised expression of TNFR1 was evident on the vascular endothelium associated with brain metastases. Human brain metastases displayed a similar TNF receptor profile compared to the mouse model. These findings describe a new approach to selectively permeabilise the BBB at sites of brain metastases, thereby enabling detection of currently invisible micrometastases and facilitating tumour-specific access of chemotherapeutic agents. We hypothesize that this permeabilisation works primarily though TNFR1 activation and, owing to the similar TNFR1 expression profiles in mouse models and human condition, the strategy has the potential for clinical translation.